Improving Immunotherapy Against B-Cell Malignancies Using γδ T-Cell–specific Stimulation and Therapeutic Monoclonal Antibodies. Issue 9 (November 2019) - Hoeres, Timm; Pretscher, Dominik; Holzmann, Elisabeth; Smetak, Manfred; Birkmann, Josef; Triebel, Jakob; Bertsch, Thomas; Wilhelm, Martin
Abstract : Tumor antigen–targeting monoclonal antibodies (mAbs) are an important element of current cancer therapies. Some of these therapeutic mAbs enable antibody-dependent cell mediated cytotoxicity (ADCC) against tumor cells. However, cancer-related functional impairment of immune effector cells may limit the clinical efficacy of antibody treatments. We reckoned that combining mAbs with cell-based immunotherapies would provide a clinically relevant synergism and benefit for cancer patients. Here, we focus on γδ T cells, as earlier studies demonstrated that γδ T-cell–based therapies are safe and promising for several types of malignancies. Similar to natural killer cells, their antitumor effects can be enhanced using antibodies, and they could, therefore, become a versatile effector cell platform for use with a variety of licensed therapeutic mAbs against cancer. In this study, we explore the potential of a combination therapy of activated γδ T cells with rituximab and the more recently developed mAbs (obinutuzumab and daratumumab) in different B-cell malignancies in vitro. Obinutuzumab outperformed the other mAbs with regard to direct target cell lysis and ADCC by γδ T cells in several CD20 + cell lines and primary lymphoma specimens. We demonstrate that comparatively few CD16 low γδ T cells are sufficient to mediate a strong ADCC. Using Fc-receptor-positive B-cell lymphomas as target cells, ADCC cannot be blocked by high concentrations of immunoglobulins or anti-CD16 antibodies, but both substances can promote cell mediated target cell lysis. This study expands on earlier reports on the therapeutic potential of distinctive tumor antigen–targeting mAbs and facilitates the understanding of the mechanism and potential of ADCC by γδ T-cell subsets. Abstract : Supplemental Digital Content is available in the text.